2013
DOI: 10.1080/17543266.2013.783629
|View full text |Cite
|
Sign up to set email alerts
|

Creative and technical design skills: are college apparel curriculums meeting industry needs?

Abstract: Rapidly advancing technology is impacting the skills required of recent college graduates who are seeking employment in the apparel industry. Therefore, strategic planning of apparel-related curriculums is vital in preparing students to meet the skill needs in the apparel industry. An online survey was conducted with the convenience sample of industry professionals in order to update an apparel design curriculum that meets the current and anticipated future needs of the industry. Sixty-three industry professio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 22 publications
0
22
0
Order By: Relevance
“…Alongside current industry dynamics, a global economic downturn and academic programme restructuring continue to create the need for a proactive stance in recruitment and retention on the part of faculty and administrators. Romeo [10] survey. Patternmaking is a current required course for technical design students, for most Global and US apparel programmes; however, the feedback from the industry indicates that few recent college graduates possess strong patternmaking skills and even fewer are able to successfully grade patterns.…”
Section: Fashion Design Educationmentioning
confidence: 99%
“…Alongside current industry dynamics, a global economic downturn and academic programme restructuring continue to create the need for a proactive stance in recruitment and retention on the part of faculty and administrators. Romeo [10] survey. Patternmaking is a current required course for technical design students, for most Global and US apparel programmes; however, the feedback from the industry indicates that few recent college graduates possess strong patternmaking skills and even fewer are able to successfully grade patterns.…”
Section: Fashion Design Educationmentioning
confidence: 99%
“…The authors' findings indicated that the leading cause for lack of success of entry-level designers was the lack of fundamental skills in clothing construction, including basic knowledge of stitches and seam types [6]. Ma YJ, et al [7] asked college students about their opinions on what information is critical for their success.…”
Section: Introductionmentioning
confidence: 99%
“…Despite advances being made by some leading designers, Computer-Aided Design (CAD) software has been slow to accommodate for the new capabilities offered by AM [9,29], making it challenging for designers to maximize their use of the technology. This is particularly evident in fashion design, an industry that has been slow to adopt three-dimensional (3D) CAD software suitable for designing parts for 3D printing [27], with the technical aspect of projects often led by designers with backgrounds in architecture or industrial design where advanced CAD software is a common part of practice [25]. Iconic 3D printed outcomes of collaboration include the Escapism Dress by Iris van Herpen (fashion designer) and Daniel Widrig (architect), the full-length gown for Dita Von Teese by Michael Schmidt (fashion designer) and Francis Bitonti (architect), and the Dive Into Me gown by Melinda Looi (fashion designer) and Samuel Canning (industrial designer).…”
Section: Introductionmentioning
confidence: 99%